Electrochemical Stability of Li6.5La3Zr1.5M0.5O12 (M = Nb or Ta) against Metallic Lithium - Kim, Yunsung; Yoo, Aeri; Schmidt, Robert; Sharafi, Asma; Lee, Heechul; Wolfenstine, Jeff; Sakamoto, Jeff (Frontiers in Energy Research, 2016)
The electrochemical stability of Li6.5La3Zr1.5Nb0.5O12 (LLZNO) and Li6.5La3Zr1.5Ta0.5O12 (LLZTO) against metallic Li was studied using direct current (DC) and electrochemical impedance spectroscopy (EIS). Dense polycrystalline LLZNO (ρ = 97%) and LLZTO (ρ = 92%) were made using sol–gel synthesis and rapid induction hot-pressing at 1100°C and 15.8 MPa. During DC cycling tests at room temperature (± 0.01 mA/cm2 for 36 cycles), LLZNO exhibited an increase in Li–LLZNO interface resistance and eventually short-circuiting while the LLZTO was stable. After DC cycling, LLZNO appeared severely discolored while the LLZTO did not change in appearance. We believe the increase in Li–LLZNO interfacial resistance and discoloration are due to reduction of Nb5+ to Nb4+. The negligible change in interfacial resistance and no color change in LLZTO suggest that Ta5+ may be more stable against reduction than Nb5+ in cubic garnet versus Li during cycling.